Problems and Efforts Transportation of Oil Palm Plantation Result Communiti in Sungai Tanang Sungai Aua Village Sungai Aua District Pasaman Barat Region - S A H N A N, S A H N A N; Rianto, M.Pd, Slamet; SE, M.Si, Nefilinda, (Pendidikan Geografi, 2014)
ABSTRACT  This study aimed to obtain information , analyze problems and efforts transportation of oil palm plantations ofthe community in Sungai Tanang Sungai Aua village Sungai Aua district Pasaman Barat Region.This study is a qualitative, conducted in Sungai Tanang Sungai Aua village Sungai Aua district Pasaman Barat Region. Informants in this study were taken purrposive sampling that farmers are already harvesting oil palm , because farmers who have crops that are having problems in transporting crops .Results showed : 1) Constraints in terms of the distance that causes the transport / transportation of oil palm plantations can only be done one time only in a single tide water, in terms of time constraints due to long distances and what means of transportation used (canoe, pontoon or motorcycle) in the transportation of oil palm plantations is done, the constraints in terms of cost due to the price of palm oil is cheap and cost less , as well as a considerable distance and what means of transportation used (canoe, pontoon or motorcycle) in transportation of oil palm plantations and constraints in terms of transportation . The use of different means of transport such as canoes, pontoon or motorcycle will affect the cost and time required in the one-time transportation and (2) efforts can be done to optimize the transportation of oil palm up to the point of sale that is by collecting advance oil that has been harvested and brought in large quantities